2008
DOI: 10.1007/s00442-008-1083-1
|View full text |Cite
|
Sign up to set email alerts
|

Complex interactions between a plant pathogen and insect parasitoid via the shared vector-host: consequences for host plant infection

Abstract: Plant viruses modify the development of their aphid vectors by inducing physiological changes in the shared host plant. The performance of hymenopterous parasitoids exploiting these aphids can also be modified by the presence of the plant pathogen. We used laboratory and glasshouse microcosms containing beans (Vicia faba) as the host plant to examine the interactions between a plant virus (pea enation mosaic virus; PEMV) and a hymenopterous parasitoid (Aphidius ervi) that share the aphid vector/host Acyrthosip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 57 publications
(63 reference statements)
3
55
0
Order By: Relevance
“…The other two factors, host plant nutritional quality and vector (aphid) performance are closely related and both can be altered by virus infection. Several viruses can modify host plant physiology by altering the concentration of carbohydrates and free aminoacids available in the phloem, changing the host plant nutritional suitability to aphids, which may have an indirect effect on their biology and performance (Fereres et al 1989;Castle and Berger 1993;Power and Gray 1995;Hodge and Powell 2008). Variation in host quality, understood as host size and growth potential at time of parasitization is the only resource limitation for the endoparasitic larval stages of aphidiid wasps.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other two factors, host plant nutritional quality and vector (aphid) performance are closely related and both can be altered by virus infection. Several viruses can modify host plant physiology by altering the concentration of carbohydrates and free aminoacids available in the phloem, changing the host plant nutritional suitability to aphids, which may have an indirect effect on their biology and performance (Fereres et al 1989;Castle and Berger 1993;Power and Gray 1995;Hodge and Powell 2008). Variation in host quality, understood as host size and growth potential at time of parasitization is the only resource limitation for the endoparasitic larval stages of aphidiid wasps.…”
Section: Discussionmentioning
confidence: 99%
“…Several aphid species have been reported to aggregate on plants infected by the pathogen (Eigenbrode et al 2002), favouring virus dispersion and suggesting a putative mutualistic interaction between plant viruses and their vectors (Gildow 1983;Fereres et al 1989;Belliure et al 2005;Stout et al 2006). Virus and aphids can interact via contest competition for plant resources and indirectly they can induce changes in plant physiology, like the activation or suppression of plant defences, which will have not only direct effects on aphids and viruses but also at the third trophic level, the aphid's natural enemies (Christiansen-Weniger et al 1998;Belliure et al 2005;Hodge and Powell 2008).…”
Section: Introductionmentioning
confidence: 98%
“…Both studies indicated that parasitoid attack and a vector escape response could lead to an increase in disease spread. Hodge and Powell (2008) showed that parasitized aphids displayed more movement than non-parasitized aphids. They suggested that the presence of parasitoids and other predators caused a "drop and move" escape response within the aphid vector populations.…”
Section: Evidence That Natural Enemies Increase Virus Transmissionmentioning
confidence: 98%
“…Recent studies (Smyrnioudis et al 2001;Hodge and Powell 2008) have shown that biological control could worsen the incidence of vector-transmitted virus disease. Both studies indicated that parasitoid attack and a vector escape response could lead to an increase in disease spread.…”
Section: Evidence That Natural Enemies Increase Virus Transmissionmentioning
confidence: 99%
“…There has been a recent growing interest in this field, demonstrating how pathogen infection in combination with herbivory may affect the foraging behavior of parasitoid wasps (Hodge & Powell, 2008;De Oliveira et al, 2014;Liu et al, 2014;Martini et al, 2014). Notably, in all cases the interactions studied are that of a pathogen, an insect vector and its parasitoid, with these being of great interest from a co-evolutionary perspective because of the tight link between pathogen and vector.…”
Section: Introductionmentioning
confidence: 99%